Investigation of Criminal Acts of Theft Based on Restorative Justice - Dwisantosa, Andi; Ma'ruf, Umar (Jurnal Hukum Khaira Ummah, 2025)
This study aims to determine and analyze the investigation of the crime of theft based on restorative justice in case Number LP/B/02/IV/2023/SPKT/Ajibarang Police/Banyumas Police/Central Java Police, the reasons for the investigation based on restorative justice, as well as the obstacles and solutions. This study uses a sociological legal approach method with the research specification being descriptive analytical. The data used are primary data and secondary data, while the data collection methods include literature studies and documentary studies. The data analysis method uses qualitative analysis. The theories used are restorative justice theory, law enforcement theory and progressive legal theory. Investigation of the crime of theft based on restorative justice in case Number LP/B/02/IV/2023/SPKT/Ajibarang Police/Banyumas Police/Central Java Police has been carried out in accordance with the Criminal Procedure Code and Police Regulation Number 8 of 2021. The reason for the investigation of the crime of theft based on restorative justice is because restorative justice can provide a more humane, fair, and solution-oriented alternative compared to the retributive approach. Obstacles in the investigation of the crime of theft based on restorative justice are the limitations of the law, the victim does not want restorative justice, there is no peace agreement, passive law enforcement officers, and lack of support from some of the community.